Aqueous surface treatment liquid for galvanized steel sheet, self-lubricating galvanized steel sheet and manufacturing method of self-lubricating galvanized steel sheet
By using aqueous surface treatment liquid on the surface of the galvanized steel plate to form an organic-inorganic composite coating, the problem of insufficient coating peeling and corrosion resistance of self-lubricated galvanized steel plate during processing is solved, and the high temperature and acid-base environment is realized. Excellent performance and paintability.
Patent Information
- Application Number
- CN202310793637.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
During the processing process, the lubricating additives of the existing self-lubricated galvanized steel plates are easy to peel off, affecting the coating performance and corrosion resistance, and are difficult to meet the requirements of high temperature and acid-base environment, resulting in the appearance of the galvanized steel plates after stamping and forming. Corrosion resistance is degraded.
The aqueous surface treatment liquid is used, including aqueous cationic polymer resin, compounded organic silane coupling agent, lubricating particles, water-soluble fluorine-containing compounds and phosphorus-containing compounds, to form an organic-inorganic composite coating to provide internal and external lubrication and corrosion resistance. By controlling the component ratio and molar ratio, the adhesion, corrosion resistance and coatingability of the coating are ensured.
The surface of the galvanized steel plate is achieved to maintain excellent lubricating performance and wear resistance after stamping and forming, while improving the coating ability and acid and alkali resistance, meeting the environmental protection and high performance requirements of galvanized steel plates in many fields.
Smart Images

Figure BDA0004314280450000121 
Figure BDA0004314280450000131 
Figure BDA0004314280450000132
Abstract
Description
Technical Field
[0001] The invention relates to a surface treatment liquid, in particular to a surface treatment liquid for galvanized steel plates. Background Art
[0002] Galvanized steel sheets are widely used in light industry, construction, home appliances, automobiles and other fields. Most of the galvanized steel sheets used in home appliances, automobile manufacturing and other fields require stamping. Due to the friction between the mold and the steel sheet, the coating is prone to powdering and blackening during forming, which not only affects the appearance quality, dimensional accuracy and corrosion resistance of the formed parts, but also aggravates the wear of the mold and reduces its service life.
[0003] In order to improve the surface wear resistance and processability of galvanized steel sheets, self-lubricating galvanized steel sheets have been developed. In addition to improving the processing and forming performance, self-lubricating galvanized steel sheets do not need to be coated with anti-rust oil to prevent galvanized steel sheets from rusting during transportation and storage. This can simplify the packaging process and reduce production and transportation costs.
[0004] The self-lubricating property of self-lubricating galvanized steel sheet is given by the organic-inorganic composite coating applied to the surface of the steel sheet, which is generally 1-3μm thick. The components forming the composite coating are mainly resin-silane compounds. In addition, in order to ensure the high lubrication performance of the coating, it is usually necessary to add a considerable amount of lubricating additives, mainly lubricating micro-powder wax, polyolefin emulsified wax, nano-MoS2, graphene, etc. These lubricating additives are usually enriched on the surface of the coating and contact the mold surface before the coating body during the processing. Through their own relative sliding, they play a role similar to lubricating oil to alleviate the wear and loss of the coating and the galvanized layer of the steel sheet during the processing. However, these lubricating additives are all low-surface energy and low-cohesive strength substances, which affect the spreading and leveling of the subsequent coating on the surface, and are prone to interlayer peeling, which reduces the adhesion of the coating to the substrate, which is not conducive to the further coating of the parts after processing. Therefore, self-lubricating galvanized sheet products are generally not recommended for post-coating.
[0005] However, in the process of using galvanized steel sheets, a considerable part of them needs to rely on subsequent coating to realize the functionalization of products such as decorative appearance and corrosion protection, so it is necessary to pay attention to the coating processing of parts after processing. Usually, the coating processing steps are as follows: after stamping and forming, the parts are subjected to short-term alkaline degreasing to remove grease and stains on the surface of the parts. Some production lines that are co-lined with galvanized bare plates or cold-rolled plates will also undergo phosphating (or ceramic) treatment, and finally electrostatic powder spraying and thermal curing. In addition, from the perspective of cost saving, the coating of many parts is only sprayed on one side for the exterior surface. However, the pH value of the alkaline degreasing agent solution in this treatment process is generally 9-11, and the pH value of the acidic phosphating (or ceramic) treatment solution is generally 2-5. In addition, the curing requires high-temperature baking curing at 180-240°C, which will damage the surface coating of the uncoated galvanized steel sheet, causing yellowing and other phenomena, thereby affecting the appearance, subsequent corrosion resistance and service performance of the coating. Therefore, the coating process has extremely high requirements on the coatability, acid and alkali resistance, and high temperature resistance of the surface treatment coating of the galvanized steel sheet, and existing self-lubricating galvanized sheet products are difficult to meet the requirements.
[0006] The Chinese patent document with publication number CN104451638A and publication date March 25, 2015, entitled “A chromium-free self-lubricating passivating agent and its preparation method”, discloses a scheme of using stearate and ethylene / vinyl acetate wax as lubricants. However, the softening point of stearate and ethylene / vinyl acetate wax lubricants is usually lower than 70°C. During the processing of parts in the OA products, home appliances and auto parts industries, the surface temperature of the continuous stamping die will be higher than 70°C, which can easily cause the lubricating function of such lubricants to be significantly reduced and fail to play a sufficient lubricating role.
[0007] The Chinese patent document with publication number CN105255338A and publication date January 20, 2016, entitled "A galvanized steel sheet and aqueous surface treatment liquid with excellent surface wear resistance, corrosion resistance and acid and alkali resistance", adopts composite lubricating particles blended with polytetrafluoroethylene particles and surface modified high-density polyethylene particles and graphene oxide to form a lubricant system. Summary of the invention
[0008] The object of the present invention is to provide an aqueous surface treatment liquid for galvanized steel sheets, which can be applied to the surface of the galvanized steel sheets and form an organic-inorganic composite coating on the surface of the galvanized steel sheets, so that the galvanized steel sheet products after surface treatment have excellent lubricity and wear resistance without reducing the coating's coatability.
[0009] In order to achieve the above object, the present invention provides an aqueous surface treatment solution for galvanized steel sheets, which comprises deionized water and a solid component; wherein the solid component comprises:
[0010] Aqueous cationic polymer resin A, the weight portion of which in the solid content is 25-65 parts;
[0011] A composite organic silane coupling agent B, whose weight portion in the solid content is 30-60 parts; wherein the composite organic silane coupling agent B is formed by mixing and hydrolyzing at least one organic silane coupling agent B1 containing an epoxy functional group and at least one organic silane coupling agent B2 containing an amino functional group, and the molar ratio of the epoxy functional group to the amino functional group in the organic silane coupling agent B1 containing an epoxy functional group and the organic silane coupling agent B2 containing an amino functional group is 2-5;
[0012] Compound lubricating particles C, whose weight parts in the solid content are 3-10 parts; wherein the compound lubricating particles C include: at least one organic silane coupling agent C1 containing unsaturated bonds; and a mixture of oxidized polyethylene wax emulsion and polytetrafluoroethylene wax emulsion;
[0013] A water-soluble fluorine-containing compound D, wherein the weight portion of fluorine element in the solid content is 1.5-5 parts;
[0014] A water-soluble phosphorus-containing compound E, wherein the weight portion of phosphorus in the solid content is 1-3 parts;
[0015] The water-soluble salt compound F containing the eighth group iron series element, wherein the weight portion of the eighth group iron series element in the solid content is 0.2-0.6 parts.
[0016] The aqueous surface treatment liquid for galvanized steel sheets of the present invention is an environmentally friendly weakly acidic aqueous surface treatment liquid that can be stably manufactured.
[0017] The aqueous cationic polymer resin A may be dispersed in water in the form of an aqueous solution, a water dispersion or an emulsion.
[0018] In the present invention, the weight of the aqueous cationic polymer resin A is controlled at 25-65 parts because, when the weight of the aqueous cationic polymer resin A is less than 25 parts, the adhesion of the formed organic-inorganic composite coating may decrease, and when the weight of the aqueous cationic polymer resin A is greater than 65 parts, the relative proportion of the silane skeleton formed by the composite organic silane coupling agent B in the organic-inorganic composite coating that plays an electrochemical anti-corrosion role on the surface of the galvanized sheet will decrease, affecting the corrosion resistance of the self-lubricating galvanized steel sheet material.
[0019] In the present invention, the weight portion of the compounded organic silane coupling agent B is 30-60 parts, because: when the weight portion of the compounded organic silane coupling agent B is less than 30 parts, the corrosion resistance of the organic-inorganic composite coating may decrease, and when it is greater than 60 parts, the relative proportion of the aqueous cationic polymer resin A in the organic-inorganic composite coating that increases the softness of the coating will decrease, affecting the T-bend and cupping performance of the organic-inorganic composite coating and the corrosion resistance after molding.
[0020] In the present invention, the molar ratio of epoxy functional groups to amino functional groups in the organosilane coupling agent containing epoxy functional groups and the organosilane coupling agent containing amino functional groups is limited to 2-5 because: during the hydrolysis process, the epoxy functional groups and amino functional groups located on different organosilane coupling agents will undergo a ring-opening reaction to form a silane skeleton network, and under normal circumstances, one amino functional group can undergo a ring-opening reaction with two epoxy functional groups. Therefore, when the molar ratio of epoxy functional groups to amino functional groups is less than 2, there will be residual amino functional groups, and the active hydrogen on the amino functional groups will further react with the water-based cationic polymer resin A, destroying the charge balance of the water-based cationic polymer resin A, causing resin agglomeration, and affecting the stability of the coating. It should be noted that a slightly excessive amount of the organosilane coupling agent containing epoxy functional groups can improve the adhesion of the final organic-inorganic composite coating to the galvanized substrate, and at the same time improve the coatability of the composite coating. When the molar ratio of epoxy functional groups to amino functional groups is greater than 5, the relative proportion of the silane skeleton that can be formed in the composite organic silane coupling agent B will decrease, affecting the corrosion resistance of the final organic-inorganic composite coating.
[0021] In the present invention, the weight proportion of the compound lubricating particles C is 3-10 parts because: if it is less than 3 parts, the lubricity and wear resistance of the coating are insufficient; if it is greater than 10 parts, too many solid lubricants exist in the film, which will significantly reduce the cohesion of the coating and may cause peeling between the coatings. In addition, the corrosion resistance and chemical resistance of the coating will also be reduced.
[0022] In the present invention, the oxidized polyethylene wax emulsion in the compound lubricating particles C is a commercial lubricating emulsion additive. After catalytic oxidation modification, this type of additive forms a certain amount of oxygen-containing polar functional groups such as carboxyl, hydroxyl and carbonyl in the surface molecular chain, which can form good compatibility with the aqueous cationic polymer resin A. In the final organic-inorganic composite coating, it mainly plays the role of internal lubrication, that is, reducing the intermolecular friction of the composite coating, playing a plasticizing role, thereby improving the heat generated by the coating during the stamping wear process and the coating fluidity. Polytetrafluoroethylene wax emulsion is also a commercial lubricating emulsion additive. This type of lubricating additive has the characteristics of high temperature resistance (high softening point), low surface energy, high hardness, and high lubricity. It quickly migrates to the coating surface during the coating baking and curing process, and mainly plays the role of external lubrication during the stamping friction process, improving the friction between the organic-inorganic composite coating and the hot metal mold surface during the stamping process, and achieving the purpose of strengthening the stamping forming performance of the coating.
[0023] In the present invention, the weight portion of the water-soluble fluorine-containing compound D is 1.5-5 parts based on the fluorine element. This is because: if the weight portion of the fluorine element is less than 1.5 parts, that is, when the fluorine compound is less, the corrosion resistance of the formed organic-inorganic composite coating may decrease; if the weight portion of the fluorine element is greater than 5 parts, that is, when there are too many fluorine compounds, due to the water-soluble characteristics of the fluorine compound, the residual fluorine compound that has not fully reacted with the galvanized interface may deteriorate the water resistance of the composite coating and affect the moisture and heat resistance and other properties.
[0024] In the present invention, the water solubility is 1-3 parts by weight of the phosphorus compound E calculated as phosphorus element. This is because: if the weight of the phosphorus element is less than 1 part, that is, when the phosphorus-containing compound is less, there is no adding effect and the corrosion resistance of the composite coating may decrease. If the weight of the phosphorus element is greater than 3 parts, that is, there are too many acidic phosphorus-containing compounds, the stability of the water treatment liquid may deteriorate.
[0025] In the present invention, the water-soluble salt compound F containing the eighth group iron element plays a role in balancing the potential of the zinc coating on the surface of the galvanized sheet, and prevents the zinc coating on the surface of the galvanized sheet from causing galvanic corrosion due to the potential imbalance between the zinc coating and the interface of the composite coating. The weight of the eighth group iron element in the solid content is 0.2-0.6 parts, because: if the weight of the eighth group iron element is less than 0.2 parts, that is, when the water-soluble salt compound containing the eighth group iron element is less, there is no addition effect, and the corrosion resistance of the composite coating may deteriorate. If the weight of the eighth group iron element is greater than 0.6 parts, that is, when the water-soluble salt compound containing the eighth group iron element is too much, a large amount of eighth group iron metal enrichment formed by substitution reaction is formed on the surface of the galvanized layer, which will reduce the adhesion between the composite coating and the galvanized layer. In addition, too much acidic salt compound containing the eighth group iron element will also cause the stability of the water treatment liquid to deteriorate.
[0026] Furthermore, the weight portion of the aqueous cationic polymer resin A can be controlled to be 35-45 parts, and the weight portion of the compounded organic silane coupling agent B can be controlled to be 40-50 parts.
[0027] Furthermore, in the aqueous surface treatment liquid of the present invention, the weight ratio of the deionized water to the solid content is 3.5-10.
[0028] When the weight ratio of deionized water to solid is less than 3.5, that is, the proportion of solid in the aqueous surface treatment liquid is too high, the storage stability of the aqueous surface treatment liquid will decrease. When the weight ratio of deionized water to solid is greater than 3.5, that is, the proportion of solid in the aqueous surface treatment liquid is too low, it is not conducive to forming an organic-inorganic composite coating with sufficient film weight on the surface of the galvanized steel plate in a single coating.
[0029] Of course, in some other embodiments of the present invention, the weight ratio of deionized water to solid content may also be less than 3.5, such as 3.
[0030] Furthermore, the aqueous surface treatment liquid of the present invention also includes a leveling agent.
[0031] Furthermore, the weight ratio of the deionized water to the leveling agent is 19-45.
[0032] In this embodiment, when the weight ratio of deionized water and the leveling agent is less than 19, that is, the proportion of the leveling agent in the aqueous surface treatment liquid is relatively high, which can easily cause the aqueous surface treatment liquid to have defects such as shrinkage holes during the coating and curing process on the galvanized steel plate surface. When the weight ratio of deionized water and the leveling agent is greater than 45, that is, the proportion of the leveling agent in the aqueous surface treatment liquid is relatively low, which can easily cause the aqueous surface treatment liquid to have problems such as poor wetting and poor leveling during the coating on the galvanized steel plate surface, thereby causing defects such as edge shrinkage, missing coating and diffraction stripes on the surface coating of the galvanized steel plate after curing.
[0033] Furthermore, in the aqueous surface treatment liquid of the present invention, the leveling agent is selected from at least one of the following: ethylene glycol butyl ether, ethylene glycol methyl ether, dipropylene glycol butyl ether, diethylene glycol monobutyl ether and isopropyl alcohol.
[0034] Furthermore, in the aqueous surface treatment liquid of the present invention, the conductivity of the deionized water is ≤10 μs / cm.
[0035] In this embodiment, the conductivity of the deionized water is limited to ≤10 μs / cm in order to further ensure the storage stability of the aqueous surface treatment liquid.
[0036] Furthermore, in the aqueous surface treatment liquid described in the present invention, the aqueous cationic polymer resin A is selected from at least one of the following: aqueous acrylic resin, aqueous epoxy resin, aqueous polyurethane resin, aqueous polyester resin and aqueous alkyd resin, and copolymer-modified resins of aqueous acrylic resin, aqueous epoxy resin, aqueous polyurethane resin, aqueous polyester resin and aqueous alkyd resin.
[0037] Furthermore, in the aqueous surface treatment liquid of the present invention, the molecular weight of the aqueous cationic polymer resin A is greater than 5000, the pH value is 3.5-7, the 100% modulus of the formed resin dry film is 50-600Mp, and the elongation at break is 100-400%.
[0038] In this embodiment, the molecular weight of the aqueous cationic polymer resin A is limited to greater than 5000, the pH value is 3.5-7, the 100% modulus of the formed resin dry film is 50-600Mp, and the elongation at break is 100-400%, which is beneficial to further improve the technical effect of this case.
[0039] When the molecular weight of the aqueous cationic polymer resin A is less than 5,000, the water resistance, solvent resistance and scratch resistance of the resin dry film may be reduced.
[0040] When the pH value of the water-based cationic polymer resin A is less than 3.5, the hydrolysis and self-polymerization rate of the compounded organic silane coupling agent B in the coating will be accelerated, affecting the stability of the coating. When the pH value is greater than 7, the acidic hydrolyzate of the compounded organic silane coupling agent B will react with the water-based cationic polymer resin A to neutralize it, destroying the charge balance of the water-based cationic polymer resin A, easily causing resin agglomeration, and affecting the stability of the coating.
[0041] The 100% modulus of the resin dry film formed by the water-based cationic polymer resin A is 50-600Mp, and the elongation at break is in the range of 100-400%, which can make the final organic-inorganic composite coating achieve a good balance between hardness and flexibility. If the 100% modulus of the resin dry film is too high, the T-bend and cupping performance of the final organic-inorganic composite coating will be reduced, and if it is too low, the solvent resistance and wear resistance of the final organic-inorganic composite coating will be reduced. If the elongation at break is too low, the corrosion resistance of the final organic-inorganic composite coating will be reduced after molding, and if it is too high, the resistance of the composite coating to solvents and chemical media will be reduced.
[0042] Furthermore, in the aqueous surface treatment liquid described in the present invention, the epoxy functional group-containing organic silane coupling agent B1 is selected from at least one of the following: 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0043] Furthermore, in the aqueous surface treatment liquid described in the present invention, the amino-functional group-containing organic silane coupling agent B2 is selected from at least one of the following: 3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropylmethyldiethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, N-(n-butyl)-3-aminopropyltrimethoxysilane and bis(3-triethoxysilylpropyl)amine.
[0044] Furthermore, in the aqueous surface treatment liquid of the present invention, the unsaturated bond in the unsaturated bond-containing organic silane coupling agent C1 is one or more of vinyl, acetoxy, vinylacryloxy and methacryloxy.
[0045] Furthermore, in the aqueous surface treatment liquid of the present invention, the weight ratio of the unsaturated bond-containing organic silane coupling agent C1 to the mixture C2 of the oxidized polyethylene wax emulsion and the polytetrafluoroethylene wax emulsion is 0.05-0.3.
[0046] In this embodiment, the weight ratio of the unsaturated bond-containing organic silane coupling agent C1 to the mixture C2 of the oxidized polyethylene wax emulsion and the polytetrafluoroethylene wax emulsion is limited to 0.05-0.3 because: the unsaturated bonds on the organic silane coupling agent will crosslink or form intermolecular forces with the oxygen-containing functional groups such as carboxyl, hydroxyl and carbonyl on the surface of the oxidized polyethylene wax and the residual vinyl, and other alkoxy groups (methoxy, ethoxy) on the organic silane will form crosslinks with the compounded organic silane coupling agent B after hydrolysis to couple the oxidized polyethylene wax in the organic-inorganic composite coating. When the weight ratio is lower than 0.05, the relative content of the at least one unsaturated bond-containing organic silane coupling agent is low, and the oxidized polyethylene wax cannot be effectively coupled in the organic-inorganic composite coating, thereby affecting the appearance, wear resistance and surface paintability of the self-lubricating galvanized steel sheet covered with the organic-inorganic composite coating after stamping. When the weight ratio is greater than 0.3, the cross-linked and polymerized brittle organosilane coupling agent will increase the surface friction coefficient of the organic-inorganic composite coating, affecting the processing lubrication performance.
[0047] Furthermore, the weight ratio of the at least one unsaturated bond-containing organic silane coupling agent C1 to the mixture of the oxidized polyethylene wax emulsion and the polytetrafluoroethylene wax emulsion may be 0.05-0.1.
[0048] Furthermore, in the aqueous surface treatment liquid of the present invention, the acid value of the oxidized polyethylene wax is in the range of 10-30, and the particle size is 50-1500 nm.
[0049] Acid value is a method to test the oxidation degree of oxidized polyethylene wax. As the oxidation degree of the oxidized wax increases, the acid value increases, the oxygen-containing functional groups such as carboxyl, hydroxyl and carbonyl increase, and the length of the carbon chain as well as the molar mass, viscosity and hardness decrease.
[0050] In this embodiment, the acid value of the oxidized polyethylene wax is in the range of 10-30 because: when the acid value of the oxidized polyethylene wax is lower than 10, the degree of oxidation is insufficient, the coupling and compatibility with the organic silane coupling agent and the polymer resin are reduced, so that the bonding force between the oxidized polyethylene wax and the coating substrate is reduced, and it is easy to peel off during friction and wear. The corrosive medium is also more likely to penetrate into the coating through the gap between the oxidized polyethylene wax and the coating substrate, affecting the wear resistance and corrosion resistance of the organic-inorganic composite coating. When the acid value of the oxidized polyethylene wax is greater than 30, the length of the carbon chain, as well as the molar mass, viscosity and hardness are reduced. Under high temperature and high load conditions, the friction coefficient will increase rapidly, affecting the wear resistance of the organic-inorganic composite coating.
[0051] In some embodiments of the present invention, the particle size (median diameter) of the oxidized polyethylene wax is limited to 50-1500nm because: if it is less than 50nm, the oxidized polyethylene wax is too small, which is not conducive to significantly reducing the dynamic friction coefficient and improving the wear resistance of the film in the final organic-inorganic composite coating, and if it is greater than 1500nm, the oxidized polyethylene wax particles are too large, and the composite coating cannot completely cover the oxidized polyethylene wax particles. A large amount of oxidized polyethylene wax exposed on the surface is prone to peeling during the stamping friction process, affecting the processing lubrication and wear resistance of the organic-inorganic composite coating. Further, the particle size (median diameter) of the oxidized polyethylene wax can be controlled in the range of 100-300nm.
[0052] Furthermore, in the aqueous surface treatment liquid of the present invention, the particle size of the polytetrafluoroethylene wax emulsion is 50-1000 nm.
[0053] In some embodiments of the present invention, the particle size (median diameter) of the polytetrafluoroethylene wax is limited to the range of 50-1000nm because: if it is less than 50nm, the polytetrafluoroethylene wax particles are too small and the wear resistance of the composite coating is not significantly improved; if it is greater than 1000nm, the polytetrafluoroethylene wax particles are too large and the composite coating cannot effectively cover the polytetrafluoroethylene wax particles. In addition, the weak bonding force between the polytetrafluoroethylene wax particles and the coating substrate causes relative sliding and peeling under low load conditions, which can easily cause the self-lubricating galvanized steel sheets transported in rolls to loosen and collapse during transportation and storage due to relative sliding between the coatings. In the case of low-load plate surface coating friction such as unwinding and slitting, the surface polytetrafluoroethylene wax particles are also prone to large-scale peeling off, resulting in "powder loss" or "de-filming" caused by the formation of a large number of peeling.
[0054] Furthermore, in the aqueous surface treatment liquid of the present invention, the weight ratio of the oxidized polyethylene wax emulsion to the polytetrafluoroethylene wax emulsion is 1-5.
[0055] In this embodiment, the weight ratio of the oxidized polyethylene wax emulsion to the polytetrafluoroethylene wax emulsion is limited to 1-5 because: if it is lower than 1, that is, more polytetrafluoroethylene wax acts as an external lubricant, and since polytetrafluoroethylene wax has the characteristics of low surface energy and weak cohesion between particles, a large amount of polytetrafluoroethylene wax will form a loose polytetrafluoroethylene layer on the surface of the composite coating. Due to the weak bonding force between the polytetrafluoroethylene wax and the coating matrix, relative sliding and peeling will occur under low load conditions, which may easily cause the self-lubricating galvanized steel sheet transported in rolls to loosen and collapse during transportation and storage due to relative sliding between the coatings. In the case of low-load plate surface coating friction such as unwinding and stripping, the surface polytetrafluoroethylene wax particles may also peel off in large quantities, forming "powdering" or "de-filming" phenomena. In addition, the low surface energy and weak cohesion of the polytetrafluoroethylene layer are not conducive to the subsequent painting, lamination and printing of the self-lubricating galvanized steel sheet parts coated with the composite coating. If it is greater than 5, that is, the polytetrafluoroethylene is too low, the polytetrafluoroethylene cannot form a good external lubrication effect on the coating surface, especially during the friction with the hot metal mold, the oxidized polyethylene wax with a lower softening point cannot provide sufficient lubrication, which will lead to insufficient wear resistance of the coating and affect the stamping performance.
[0056] Furthermore, in the aqueous surface treatment liquid of the present invention, the water-soluble fluorine-containing compound D comprises: at least one of a fluorine-containing metal acid, a fluorometallate and a fluoride.
[0057] In some embodiments, illustratively, the water-soluble fluorine-containing compound D can be one or more of: fluorotitanic acid, fluorozirconic acid, fluorosilicic acid, ammonium fluorotitanate, sodium fluorotitanate, potassium fluorotitanate, ammonium fluorozirconate, sodium fluorozirconate, potassium fluorozirconate, sodium fluorosilicate, sodium fluoride, ammonium fluoride and potassium fluoride.
[0058] Furthermore, in the aqueous surface treatment liquid of the present invention, the water-soluble phosphorus-containing compound E includes: hydrogen phosphate and / or phosphoric acid.
[0059] In some embodiments, illustratively, the water-soluble phosphorus-containing compound E may be one or more of: ammonium dihydrogen phosphate, zinc dihydrogen phosphate, manganese dihydrogen phosphate, phosphoric acid, phytic acid, and hydroxyethylidene diphosphonic acid.
[0060] Furthermore, in the aqueous surface treatment liquid described in the present invention, the water-soluble salt compound F containing the eighth group iron-based elements is an iron-based metal salt, which is selected from at least one of the following: cobalt nitrate, nickel nitrate, iron nitrate, cobalt acetate, nickel acetate, iron acetate, cobalt citrate and iron citrate.
[0061] Another object of the present invention is to provide a self-lubricating galvanized steel sheet having excellent surface paintability, corrosion resistance and surface wear resistance, which can meet the requirements of users in multiple fields for environmental protection, surface wear resistance, stamping formability, paintability and resistance to degreasing and phosphating treatment of galvanized steel sheets. The self-lubricating galvanized steel sheet also has good resistance to various chemical media, such as resistance to wiping with organic solvents.
[0062] Specifically, surface coating properties include steel plate surface energy, epoxy powder coating adhesion, alkyd resin coating adhesion and precision ink printing adhesion; surface wear resistance includes the appearance after high-load and high-temperature sliding friction and the appearance after multiple friction of different materials such as polyurethane gaskets and corrugated paper; corrosion resistance includes flat plate corrosion resistance, corrosion resistance after molding, corrosion resistance after scratching and damage, and corrosion resistance after degreasing and phosphating; resistance to various chemical media includes acid and alkali resistance, that is, resistance to alkaline degreasing agents and acid phosphating liquids and ceramic treatment liquids, resistance to organic solvent wiping, that is, resistance to the appearance after multiple wiping with gauze adsorbed with 80% ethanol solution and butanone solution.
[0063] Through research, the inventors found that the above-mentioned purpose of the invention can be achieved by coating and curing the aqueous surface treatment liquid as described above on the surface of the galvanized steel sheet.
[0064] Based on this, the present invention also provides a self-lubricating galvanized steel sheet, the surface of which has a composite coating formed by coating the aqueous surface treatment liquid as described above.
[0065] In the self-lubricating galvanized steel sheet described in the present invention, the composite coating is a single-layer structure.
[0066] Furthermore, in the self-lubricating galvanized steel sheet of the present invention, the single-side film weight of the composite coating is 0.5-2 g / m 2 .
[0067] In this embodiment, the film weight of the composite coating is controlled to be 0.5-2 g / m2 Because: when less than 0.5g / m 2 When the coating is thin, the wear resistance, corrosion resistance and acid and alkali resistance of the coating may decrease. The coating thickness exceeds 2g / m 2 On the one hand, the surface treatment cost per unit area will increase. On the other hand, due to the thicker coating, the cohesion of the coating may decrease and the wear resistance may decrease.
[0068] Another object of the present invention is to provide a method for manufacturing a self-lubricating galvanized steel sheet.
[0069] Based on the above invention object, the present invention also provides a method for manufacturing a self-lubricating galvanized steel sheet, comprising the steps of:
[0070] Applying the aqueous surface treatment liquid on the surface of the galvanized steel sheet;
[0071] The aqueous surface treatment liquid is cured to form a composite coating on the surface of the galvanized steel sheet.
[0072] In the manufacturing method of the present invention, the method of coating the aqueous surface treatment liquid on the galvanized steel sheet may include roller coating, dipping or spraying.
[0073] In the manufacturing method described in the present invention, there is no particularly strict restriction on the curing method of the aqueous surface treatment liquid coated on the surface of the galvanized steel plate, and hot air heating, induction heating, infrared heating or combined heating can be used.
[0074] The water-based surface treatment liquid can be applied to one or both sides of the galvanized steel sheet.
[0075] Furthermore, in the manufacturing method of the present invention, the curing temperature is 80-180°C.
[0076] In this embodiment, the aqueous surface treatment liquid is cured at a temperature of 80-180°C because: 80-180°C can volatilize the solvent water and low-boiling point additives in the aqueous surface treatment liquid, promote the cross-linking film formation of the aqueous cationic polymer resin A and the compounded organic silane coupling agent B, when the curing temperature is lower than 80°C, the cross-linking of the organic-inorganic composite coating formed by the curing of the surface treatment liquid is not sufficient, which may lead to a decrease in the adhesion of the coating on the surface of the galvanized steel plate, and when the curing temperature is higher than 180°C, on the one hand, the energy consumption cost of the surface treatment of the steel plate will increase, and on the other hand, the cross-linking degree of the silane in some composite coatings increases with the temperature, which has an adverse effect on the corrosion resistance and paintability of the coating after deformation.
[0077] The aqueous surface treatment liquid for galvanized steel sheets and the self-lubricating galvanized steel sheets of the present invention have the following characteristics and beneficial effects:
[0078] The present invention adopts water-based cationic polymer resin and compounded organic silane coupling agent as the matrix of the composite coating to achieve the effect of preventing the physical penetration of corrosive media and inhibiting the occurrence of electrochemical corrosion, so that the formed composite coating has excellent corrosion resistance and acid and alkali resistance. The present invention adopts compounded lubricating particles to provide external lubrication and internal lubrication of the composite coating at the same time, that is, a certain amount of oxygen-containing polar functional groups such as carboxyl, hydroxyl and carbonyl are formed in the molecular chain of the surface of the oxidized polyethylene wax particle size. After appropriate silane coupling modification, it can simultaneously form good compatibility with the silane skeleton formed by the water-based cationic polymer resin A and the compounded organic silane coupling agent B, so that the oxidized polyethylene wax particles are uniformly dispersed in the coating and form a strong bond with the coating, while providing the internal lubrication of the coating, the cohesive bonding force of the coating itself is not reduced.
[0079] The aqueous surface treatment liquid of the present invention does not contain chromium and is an environmentally friendly surface treatment agent. After surface treatment of the galvanized steel sheet, the surface of the galvanized steel sheet has excellent paintability, corrosion resistance and surface wear resistance.
[0080] In the present invention, a certain amount of polytetrafluoroethylene wax particles are distributed on the coating surface to play the role of external lubrication, thereby improving the friction between the composite coating and the hot metal mold surface during the stamping process.
[0081] In a further preferred technical solution, by reasonably controlling the weight ratio of polytetrafluoroethylene wax to oxidized polyethylene wax, it is possible to provide excellent lubrication and wear resistance without reducing the coatability of the coating.
[0082] In a further preferred technical solution, an aqueous cationic polymer resin system having both a higher modulus and a higher elongation is selected, such as an aqueous cationic polycarbonate-modified polyurethane, so that the coating has both flexibility and hardness, thereby improving the problems of poor wear resistance and corrosion resistance after processing deformation of such galvanized surface treatment coatings.
[0083] In a further preferred technical solution, the compounded organosilane coupling agent increases the density of the silane skeleton in the composite coating by pre-crosslinking with organosilane coupling agents containing epoxy functional groups and amino functional groups, and a slightly excess of organosilane coupling agents containing epoxy functional groups migrate to the coating surface and the interface with the galvanized layer, thereby enhancing the corrosion resistance, adhesion and paintability of the coating. DETAILED DESCRIPTION
[0084] The aqueous surface treatment liquid for galvanized steel sheets, the self-lubricating galvanized steel sheets and the method for manufacturing the same described in the present invention will be further explained and illustrated below in conjunction with specific embodiments. However, such explanation and illustration do not constitute an improper limitation on the technical solution of the present invention.
[0085] Examples 1-38 and Comparative Examples 1-6
[0086] In order to verify the technical effect of the present invention, the inventors prepared aqueous surface treatment liquids of Examples 1-38 and surface treatment liquids of Comparative Examples 1-6 accordingly.
[0087] Tables 1-1 and 1-2 list the components and contents of the solids in the aqueous surface treatment liquids of Examples 1-38 and Comparative Examples 1-6, as well as the types and contents of the leveling agents.
[0088] Table 1-1.
[0089]
[0090]
[0091] Table 1-2.
[0092]
[0093]
[0094] Note:
[0095] A1 is a waterborne polycarbonate modified polyurethane, which is a copolymer modified resin of a waterborne polyurethane resin, with a molecular weight of 8000-10000, a pH value of 5, a 100% modulus of the formed resin dry film of 200Mp, and an elongation at break of 320%; A2 is a waterborne acrylic resin, with a molecular weight of 6000-80000, a pH value of 3.5, a 100% modulus of the formed resin dry film of 300Mp, and an elongation at break of 120%; A3 is a waterborne epoxy resin, with a molecular weight of 10000-15000, a pH value of 6.5, a 100% modulus of the formed resin dry film of 500Mp, and an elongation at break of 100%; A4 is a waterborne alkyd resin, with a molecular weight of 5000-8000, a pH value of 7, a 100% modulus of the formed resin dry film of 50Mp, and an elongation at break of 300%;
[0096] B1-1 is 3-glycidyloxypropyltriethoxysilane, B1-2 is 3-glycidyloxypropylmethyldiethoxysilane, B1-3 is 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane; B2-1 is 3-aminopropyltriethoxysilane, B2-2 is 3-aminopropylmethyldimethoxysilane, B2-3 is N-2-aminoethyl-3-aminopropyltriethoxysilane, and B2-4 is bis(3-triethoxysilylpropyl)amine;
[0097] C1-1 is vinyl triethoxysilane, C1-2 is 3-acetoxypropyl trimethoxysilane, C1-3 is 3-methacryloxypropyl triethoxysilane, C2 represents oxidized polyethylene wax emulsion, C2-1 is an oxidized polyethylene wax emulsion with a median diameter of 200 nm and an acid value of 30, C2-2 is an oxidized polyethylene wax emulsion with a median diameter of 1500 nm and an acid value of 10, and C3 is a polytetrafluoroethylene wax emulsion with a median diameter of 100 nm; of course, in other embodiments, polytetrafluoroethylene wax emulsions with a particle size of 50-1000 nm are feasible.
[0098] D1 is fluorotitanic acid, D2 is ammonium fluorotitanate, and D3 is ammonium fluorozirconate; E1 is ammonium dihydrogen phosphate, E2 is phytic acid, and E3 is hydroxyethylidene diphosphonic acid; F1 is cobalt nitrate, F2 is nickel nitrate, and F3 is cobalt citrate.
[0099] The “*” in Comparative Examples 3 and 6 indicates that tap water was used instead of deionized water.
[0100] In addition, although the aqueous cationic polymer resins A in the above embodiments only provide four types, namely A1, A2, A3 and A4, in other embodiments, other aqueous cationic polymer resins may also be selected, for example, aqueous polyurethane resins, aqueous polyester resins, copolymer-modified resins of aqueous acrylic resins, aqueous epoxy resins, aqueous polyester resins and aqueous alkyd resins, and combinations of all these substances.
[0101] The galvanized steel sheet was treated with the aqueous surface treatment liquid of the above embodiments and comparative examples according to the following steps:
[0102] (1) The substrates of Examples 1-38 and Comparative Examples 1-6 are all 0.6 mm thick galvanized steel sheets, and the weight of the zinc layer on both sides of the galvanized steel sheets is 60 g / m 2 The steel plate surface was degreased by solvent. The steel plate surface was first wiped with gauze soaked in heptane to remove the anti-rust oil on the steel plate surface, then ultrasonicated in ethanol solution for 20 minutes, and finally washed with pure water to remove the residual organic solvent components on the surface, and then dried for use.
[0103] (2) The aqueous surface treatment liquids of Examples 1-38 and Comparative Examples 1-6 are applied to the surface of the galvanized steel sheet and cured and dried at 80-180° C. to form a film with a weight of 0.5-2 g / m 2 Composite coating.
[0104] It should be noted that the present invention focuses on the excellent performance of the composite coating formed by the designed aqueous surface treatment liquid, and there is no special limitation on the galvanized substrate used. In actual application, technicians in this field can select the required galvanized steel plate according to specific needs.
[0105] Table 2 lists the curing temperature and film weight of the self-lubricating galvanized steel sheets of Examples 1-38 and Comparative Examples 1-6.
[0106] Table 2.
[0107]
[0108]
[0109] In order to verify the superior implementation effect of the aqueous surface treatment liquid designed by the present invention, the self-lubricating galvanized steel sheets of Examples 1-38 and Comparative Examples 1-6 prepared were sampled and cut into standard size samples and subjected to the following tests, thereby obtaining test data for evaluating their various properties. The specific test items and test methods are as follows:
[0110] 1) Flat plate corrosion resistance:
[0111] According to the ASTM-B117 standard, the flat plate was subjected to a salt spray test for 168 hours. The evaluation criteria were:
[0112] ◎: White rust area ratio is less than 5%
[0113] ○: White rust area ratio is greater than 5% and less than 10%
[0114] Δ: White rust area ratio is greater than 10% and less than 50%
[0115] ×: White rust area ratio is greater than 50%
[0116] 2) Corrosion resistance after forming:
[0117] Use Ericsson cupping instrument to perform 8mm cupping, and conduct salt spray test on the cupping part. The test standard is ASTM-B177, the test time is 96h, and the evaluation criteria are:
[0118] ◎: The white rust area ratio of the cupping part is less than 5%
[0119] ○: The white rust area ratio of the cupping part is greater than 5% and less than 10%
[0120] Δ: The white rust area ratio of the cupping part is greater than 10% and less than 50%
[0121] ×: The white rust area ratio of the cupping part is greater than 50%
[0122] 3) Corrosion resistance after scribing:
[0123] Use a surgical blade to cross-scribe with a length of 60 mm and a cross angle of 60 degrees, and scratch through the passivation layer but not the metal coating. Perform a salt spray test on the flat sample after the scribing. The test standard is ASTM-B177 and the test time is 96 hours. The evaluation criteria are:
[0124] ◎: White rust area ratio is less than 5%
[0125] ○: White rust area ratio is greater than 5% and less than 10%
[0126] Δ: White rust area ratio is greater than 10% and less than 50%
[0127] ×: White rust area ratio is greater than 50%
[0128] 4) Corrosion resistance after alkali washing:
[0129] Use a medium alkalinity degreasing agent (pH: 9-11) for cleaning, spray at 50°C for 2 minutes, and then clean the surface with deionized water and conduct a salt spray test. The test standard is ASTM-B177 and the test time is 96 hours. The evaluation criteria are:
[0130] ◎: White rust area ratio is less than 5%
[0131] ○: White rust area ratio is greater than 5% and less than 10%
[0132] Δ: White rust area ratio is greater than 10% and less than 50%
[0133] ×: White rust area ratio is greater than 50%
[0134] 5) Stamping formability:
[0135] A self-made high-temperature sliding friction performance test device for coated steel plates (publication number: CN114813421A) was used. Experimental conditions: load 1000KN, temperature setting: 80°C, indenter material: SKD die steel (R0.5), indenter length: 4mm, friction distance: 50mm, speed: 200mm / s, evaluation criteria:
[0136] ◎: No change in appearance
[0137] ○: A few black spots on the surface
[0138] Δ: There are many obvious black stripes on the surface
[0139] ×: The appearance is completely black
[0140] 6) Wear resistance:
[0141] Use the Esrui multifunctional wear tester, friction pair materials: ① polyurethane gasket and ② corrugated paper, test load: 50g, travel distance 30mm, test speed: 50 times / min, repeated wear 50 times, evaluation criteria:
[0142] ◎: No change in coating
[0143] ○: Slight scratches on the coating
[0144] Δ: Multiple scratches on the coating
[0145] ×: The coating is completely peeled off
[0146] 7) Resistance to organic solvent wiping:
[0147] ① Use gauze moistened with 80% alcohol to rub the surface of the steel plate back and forth 30 times. Evaluation criteria:
[0148] ◎: No change in appearance
[0149] ○: Slight marks on the exterior
[0150] Δ: The appearance is obviously whitened and the coating is partially dissolved
[0151] ×: The coating is completely dissolved
[0152] ② Use gauze moistened with butanone to rub the surface of the steel plate back and forth 20 times. Evaluation criteria:
[0153] ◎: No change in appearance
[0154] ○: Slight marks on the exterior
[0155] Δ: The appearance is obviously whitened and the coating is partially dissolved
[0156] ×: The coating is completely dissolved
[0157] 8) Acid and alkali resistance:
[0158] ① Alkali resistance: Soak in a 1% NaOH solution at room temperature for 10 minutes, rinse with water and visually observe the changes in surface appearance. Evaluation criteria:
[0159] ◎: No change in appearance
[0160] ○: Slight marks on the exterior
[0161] Δ: The appearance is obviously whitened and the coating is partially dissolved
[0162] ×: The coating is completely dissolved
[0163] ② Acid resistance: Soak in a 1% HCl solution at room temperature for 10 minutes, rinse with water and visually observe the changes in surface appearance. Evaluation criteria:
[0164] ◎: No change in appearance
[0165] ○: Slight marks on the exterior
[0166] Δ: The appearance is obviously whitened and the coating is partially dissolved
[0167] ×: The coating is completely dissolved
[0168] 9) Paintability:
[0169] The surface treated galvanized steel sheet was sprayed in a 50℃ alkaline degreasing agent (pH: 9-11) for 2 minutes, the surface was cleaned with deionized water, and then dried in a 140℃ oven for 15 minutes. After coating according to the following conditions, the coating adhesion test was carried out. Test conditions:
[0170] ① Alkyd white paint (product of Shanghai Zhenhua Paint Factory, brand: A-09), 22# rod coating, baking conditions: 140℃ baking for 40min;
[0171] ② Epoxy powder coating (Akzo Nobel product, brand: EA05BH), powder coating thickness 70-80μm, baking conditions: 200℃ baking for 10min;
[0172] ③ Ink (Japan Seiko ink, brand: 1300EX), 12# rod coating, dry film 10-12μm, baking conditions: 120℃ baking for 20min;
[0173] After applying the above coating and ink, use an Erichsen 295 cross-hatch knife to scratch 100 small grids with a size of 1 mm on the surface of the coating. 2 The depth should penetrate the paint film layer to reach the surface of the steel plate. After peeling with 3M610 tape, observe the damage of the paint film and the number of residual grids. Evaluation criteria:
[0174] ◎: The cutting edge is completely smooth, without any falling off
[0175] ○: A small amount of coating falls off at the intersection of the cuts, but the cross-cut area affected cannot be more than 5%
[0176] Δ: Coating peels off at the intersection of the cuts and / or along the edges of the cuts, and the affected cross-cut area is significantly greater than 5%, but not significantly greater than 15%
[0177] ×: Coating peeled off at the intersection of the cuts and / or along the edges of the cuts, and the affected cross-cut area is significantly greater than 15%.
[0178] Table 3 lists the relevant performance parameters of the self-lubricating galvanized steel sheets of Examples 1-38 and Comparative Examples 1-6 after the above tests.
[0179] Table 3.
[0180]
[0181] It can be seen from Table 3 that after the galvanized steel sheets in Examples 1-38 were subjected to the above tests, the evaluation results were all "◎" and "○", especially for various coatings and printing media such as alkyd coatings, epoxy powders and inks, they all had good coatability. This shows that the galvanized steel sheets coated with the aqueous surface treatment liquid of the present invention not only have the stamping formability of self-lubricating steel sheets, but also have excellent comprehensive properties such as surface coatability, corrosion resistance (flat plate, after forming, after scribing and after alkali washing), wear resistance and solvent resistance.
[0182] Combining Table 1 and Table 3, it can be seen that compared with Examples 1-38, since the content of aqueous cationic resin A in the surface treatment liquid of Comparative Example 1 is too low, the film-forming property, corrosion resistance and coatability of the applied surface treatment liquid after drying are poor.
[0183] In Comparative Example 2, since the content of the compounded organic silane coupling agent B in the surface treatment liquid is too low and the baking and curing temperature is too low, the adhesion, corrosion resistance, stamping formability and comprehensive resistance of the coating are all poor.
[0184] In Comparative Example 3, due to the presence of incompletely reacted amino functional groups in the composite organic silane coupling agent B, the performance of the water-based cationic resin A was affected, so the film-forming property, corrosion resistance, comprehensive resistance and coatability of the applied surface treatment liquid after drying were poor.
[0185] In Comparative Example 4, since the composite organic silane coupling agent B failed to form an effective skeleton network due to the silane ratio problem, the corrosion resistance and comprehensive resistance of the coating were poor.
[0186] Since the content of the compound lubricating particles C in Comparative Examples 5 and 6 does not meet the requirements of the present invention, a good internal and external lubrication coordination cannot be formed, resulting in poor stamping processability and wear resistance of the coating.
[0187] It can be seen from this that the self-lubricating galvanized steel sheet formed by coating the aqueous surface treatment liquid of the present invention on the surface of the galvanized steel sheet has excellent surface paintability, corrosion resistance, surface wear resistance, and comprehensive resistance to chemical solvents, acids and alkalis, etc., and can meet the requirements of users in many fields for environmentally friendly raw materials of galvanized steel sheets, intensive and green processing (stamping processability, paintability), and excellent service performance (corrosion resistance and comprehensive resistance).
[0188] It should be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with by those skilled in the art from the contents disclosed in the present invention, and all should belong to the protection scope of the present invention.
Claims
1. An aqueous surface treatment solution for galvanized steel sheets, comprising deionized water and solids; characterized in that: The solid content includes: Aqueous cationic polymer resin A, the weight portion of which in the solid content is 25-65 parts; A composite organic silane coupling agent B, whose weight portion in the solid content is 30-60 parts; wherein the composite organic silane coupling agent B is formed by mixing and hydrolyzing at least one organic silane coupling agent B1 containing an epoxy functional group and at least one organic silane coupling agent B2 containing an amino functional group, and the molar ratio of the epoxy functional group to the amino functional group in the organic silane coupling agent B1 containing an epoxy functional group and the organic silane coupling agent B2 containing an amino functional group is 2-5; Compound lubricating particles C, whose weight parts in the solid content are 3-10 parts; wherein the compound lubricating particles C include: at least one organic silane coupling agent C1 containing unsaturated bonds; and a mixture of oxidized polyethylene wax emulsion and polytetrafluoroethylene wax emulsion; A water-soluble fluorine-containing compound D, wherein the weight portion of fluorine element in the solid content is 1.5-5 parts; A water-soluble phosphorus-containing compound E, wherein the weight portion of phosphorus in the solid content is 1-3 parts; The water-soluble salt compound F containing the eighth group iron series element, wherein the weight portion of the eighth group iron series element in the solid content is 0.2-0.6 parts.
2. The aqueous surface treatment liquid according to claim 1, characterized in that The weight ratio of the deionized water to the solid content is 3.5-10.
3. The aqueous surface treatment liquid according to claim 1, characterized in that Also includes leveling agents.
4. The aqueous surface treatment liquid according to claim 3, characterized in that The weight ratio of the deionized water to the leveling agent is 19-45.
5. The aqueous surface treatment liquid according to claim 3, characterized in that The leveling agent is selected from at least one of the following: ethylene glycol butyl ether, ethylene glycol methyl ether, dipropylene glycol butyl ether, diethylene glycol monobutyl ether and isopropyl alcohol.
6. The aqueous surface treatment liquid according to claim 1, characterized in that The conductivity of the deionized water is ≤10 μs / cm.
7. The aqueous surface treatment liquid according to claim 1, characterized in that The aqueous cationic polymer resin A is selected from at least one of the following: aqueous acrylic resin, aqueous epoxy resin, aqueous polyurethane resin, aqueous polyester resin and aqueous alkyd resin, and copolymer-modified resins of aqueous acrylic resin, aqueous epoxy resin, aqueous polyurethane resin, aqueous polyester resin and aqueous alkyd resin.
8. The aqueous surface treatment liquid according to claim 1, characterized in that The molecular weight of the aqueous cationic polymer resin A is greater than 5000, the pH value is 3.5-7, the 100% modulus of the formed resin dry film is 50-600Mp, and the elongation at break is 100-400%.
9. The aqueous surface treatment liquid according to claim 1, characterized in that: The epoxy-functional organic silane coupling agent B1 is selected from at least one of the following: 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
10. The aqueous surface treatment liquid according to claim 1, characterized in that The amino-functional organic silane coupling agent B2 is selected from at least one of the following: 3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropylmethyldiethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, N-(n-butyl)-3-aminopropyltrimethoxysilane and bis(3-triethoxysilylpropyl)amine.
11. The aqueous surface treatment liquid according to claim 1, characterized in that The unsaturated bond in the unsaturated bond-containing organic silane coupling agent C1 is one or more of vinyl, acetoxy, vinyl acyloxy and methacryloxy.
12. The aqueous surface treatment liquid according to claim 1, characterized in that The weight ratio of the unsaturated bond-containing organic silane coupling agent C1 to the mixture of the oxidized polyethylene wax emulsion and the polytetrafluoroethylene wax emulsion is 0.05-0.
3.
13. The aqueous surface treatment liquid according to claim 1, characterized in that: The acid value of the oxidized polyethylene wax is in the range of 10-30, and the particle size is 50-1500nm.
14. The aqueous surface treatment liquid according to claim 1, characterized in that The particle size of the polytetrafluoroethylene wax emulsion is 50-1000nm.
15. The aqueous surface treatment liquid according to claim 1, characterized in that: The weight ratio of the oxidized polyethylene wax emulsion to the polytetrafluoroethylene wax emulsion is 1-5.
16. The aqueous surface treatment liquid according to claim 1, characterized in that The water-soluble fluorine-containing compound D comprises at least one of a fluorine-containing metal acid, a fluorometallate and a fluoride.
17. The aqueous surface treatment liquid according to claim 1, characterized in that: The water-soluble phosphorus-containing compound E includes: hydrogen phosphate and / or phosphoric acid.
18. The aqueous surface treatment liquid according to claim 1, characterized in that The water-soluble salt compound F containing the eighth group iron series element is selected from at least one of the following: cobalt nitrate, nickel nitrate, iron nitrate, cobalt acetate, nickel acetate, iron acetate, cobalt citrate and iron citrate.
19. A self-lubricating galvanized steel sheet, characterized in that: The surface of the galvanized steel sheet has a composite coating formed by coating the aqueous surface treatment liquid as described in any one of claims 1-18.
20. The self-lubricating galvanized steel sheet according to claim 19, characterized in that: The single-sided film weight of the composite coating is 0.5-2 g / m 2 .
21. The method for manufacturing a self-lubricating galvanized steel sheet according to claim 19 or 20, characterized in that: Includes steps: Applying the aqueous surface treatment liquid on the surface of the galvanized steel sheet; The aqueous surface treatment liquid is cured to form a composite coating on the surface of the galvanized steel sheet.
22. The manufacturing method according to claim 21, characterized in that: The curing temperature is 80-180°C.
Citation Information
Patent Citations
Self-lubricating chromium-free passivator and preparation method thereof
CN104451638A
Galvanized steel sheet excellent in surface abrasion resistance, corrosion resistance and acid and base resistance and water-based surface treating agent
CN105255338A
High-temperature sliding friction performance testing device for coated and plated steel plate and control system
CN114813421A
Compound composition and process for surface treating of metal material
CN1814860A
Cited By
A pre-lubricated steel sheet having excellent formability and a method for producing the same
CN122668570A
Galvanized steel plate having good adhesion to electron beam cured coating, and manufacturing method therefor
WO2026114155A1